Distorsi Metode Penafsiran Al-Qur’an: Studi Kritis Jargon Kembali Kepada Al-Qur’an - Muhammad Dahlan; Ahmad Syukron; M. Ziyadul Haq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study analyzes the implications of the slogan “returning to the Qur’an,” which is frequently understood as a call to rely directly on the Qur’an in addressing religious and social issues while neglecting essential exegetical disciplines such as tafsir, asbāb al-nuzūl, and other authoritative scholarly frameworks. The discussion is reinforced by the findings of Husnul Maab, a postgraduate student at the Institut Ilmu Al-Qur’an (IIQ), whose thesis on the textuality of Qur’anic interpretation and its relationship to religious diversity in Indonesia highlights the serious problems inherent in literalist approaches, particularly in the interpretation of verses related to jihad and politics. This research employs a qualitative library research method, using relevant literature as the primary source of data and analysis, requiring in-depth understanding and critical engagement with the subject matter. The findings indicate that the slogan “returning to the Qur’an” can function as a form of interpretive distortion when it is not accompanied by adequate scholarly competence. Attempts to deepen Qur’anic understanding without integrating the bayānī (textual), burhānī (rational), and ‘irfānī (ethical–spiritual) approaches tend to result in rigid and reductionist interpretations. Such purely textual readings represent an extreme position that may lead to harmful consequences, including the tendency to label others as unbelievers, sinners, or wrongdoers solely due to interpretive differences. Ultimately, religious understanding shaped by reactive and exclusionary interpretations poses a significant threat to religious pluralism and social harmony in Indonesia.